An evaluation of pharmacists' general attitudes, knowledge, and phobias regarding medications that include corticosteroids: a cross-sectional study - Muna Barakat; Samar Thiab; Rana Abu Farha; Anas O. Alshweiki; Roa'a Thaher; Asem Alsughaier; Diana Malaeb (BMC, 2024)
Abstract Background Corticosteroid-containing medications are widely accessible in various forms, including topical, injectable, and inhaled formulations. Due to uncertain safety profiles, healthcare providers, including pharmacists, often express apprehension when dispensing these drugs. This cross-sectional study assesses the knowledge, attitudes, and phobia of Jordanian pharmacists regarding corticosteroid-containing medications. Methods Conducted through a self-administered online questionnaire. Results the study reveals that dermatological conditions and respiratory disorders are the primary indications for prescribing corticosteroid-containing drugs. The most reported side effects among pharmacists' patients include increased appetite, diabetes, and skin thinning. Pharmacists generally exhibit acceptable knowledge, with a median score of 9.0 out of 11.0 (IQR = 3.0). Over two-thirds of pharmacists (69.9%) achieve a high knowledge score (Bloom's cut-off point ≥ 8.8). However, only 55.7% are aware that corticosteroids may induce mood changes. High phobia scores, particularly concerning increased blood pressure and osteoporosis risks, indicate pharmacist reservations in corticosteroid dispensing. Interestingly, pharmacists in rural areas display lower knowledge scores, while those working outside community pharmacies exhibit lower phobia scores compared to their counterparts in urban areas and community pharmacies, respectively. Conclusion Despite generally good knowledge levels, the study underscores high phobia scores among Jordanian pharmacists regarding corticosteroid dispensing, particularly due to concerns about blood pressure elevation and osteoporosis risks. This suggests a potential need for targeted educational interventions and support systems to enhance pharmacist confidence and optimize corticosteroid usage while minimizing associated risks.